Adult Development: Capturing New Ways of Thinking About the Life Course - Rosemary S. Caffarella; M. Carolyn Clark; Florence Guido-DiBrito; Sharan B. Merriam; Marsha Rossiter; Kathleen Taylor; Elizabeth J. Tisdell (Adult Education Research Conference, 2000)
We outline first a brief overview of a four-fold typology of developmental theory (biological, psychological, sociocultural an integrative models). We then discuss work that illustrates two of these frames: the sociocultural, which includes racial and ethnic, and relational aspects of development; and the integrative, focusing on time, development as narrative, and spiritual development. We close with a commentary on the current developmental literature and how this literature challenges our practice as adult educators.